Biometric and technologic aspects of experimental technologies in mandible endografting with composite TiNi-based materials - N. M. Dyuryagin; P. G. Sysolyatin; I. D. Tazin; Ye. N. Dyuryagina; E. V. Gunther; O. D. Baidik (Бюллетень сибирской медицины)
Mandibular defect experimental endografting has been performed with the use of composite TiNi-based materials. An ability to create the artificial alive biological models was proved to act high-efficiently in the mandible perpetually. When designing the reconstructive mandibular models made of TiNi-based material for longlife usage it’s to be complied thoroughly the methodology and technology of individual approach. Experimental research results are recommended for investigation and application when creating anthropological mandibular models in the wide clinical practice.